Clinico-pathological features in fatal COVID-19 infection: a preliminary experience of a tertiary care center in North India using postmortem minimally invasive tissue sampling. (3rd October 2021) - Ray, Animesh; Jain, Deepali; Goel, Ayush; Agarwal, Shubham; Swaroop, Shekhar; Das, Prasenjit; Arava, Sudheer Kumar; Mridha, Asit Ranjan; Nambirajan, Aruna; Singh, Geetika; Arulselvi, S.; Mathur, Purva; et al.
ABSTRACT: Objectives: To study the histopathology of patients dying of COVID-19 using post-mortem minimally invasive sampling techniques. Methods: This was a single-center observational study conducted at JPNATC, AIIMS. Thirty-seven patients who died of COVID-19 were enrolled. Post-mortem percutaneous biopsies were taken from lung, heart, liver, kidney and stained with hematoxylin and eosin. Immunohistochemistry was performed using CD61 and CD163. SARS-CoV-2 virus was detected using IHC with primary antibodies. Results: The mean age was 48.7 years and 59.5% were males. Lung histopathology showed diffuse alveolar damage in 78% patients. Associated bronchopneumonia was seen in 37.5% and scattered microthrombi in 21% patients. Immunopositivity for SARS-CoV-2 was observed in Type II pneumocytes. Acute tubular injury with epithelial vacuolization was seen in 46% of renal biopsies. Seventy-one percent of liver biopsies showed Kupffer cell hyperplasia and 27.5% showed submassive hepatic necrosis. Conclusions: Predominant finding was diffuse alveolar damage with demonstration of SARS-CoV-2 protein in the acute phase. Microvascular thrombi were rarely identified in any organ. Substantial hepatocyte necrosis, Kupffer cell hypertrophy, microvesicular, and macrovesicular steatosis unrelated to microvascular thrombi suggested that liver might be a primary target of COVID-19.